2017
DOI: 10.3892/etm.2017.5091
|View full text |Cite
|
Sign up to set email alerts
|

High expression of long chain acyl‑coenzyme A synthetase�1 in peripheral blood may be a molecular marker for assessing the risk of acute myocardial infarction

Abstract: The current study aimed to investigate whether the increased expression of long chain acyl-coenzymeA synthetase 1 (ACSL1) in peripheral blood leukocytes (PBL) may be a molecular marker for the genetic evaluation of acute myocardial infarction (AMI). The mechanism of action of ACSL1 in the pathogenesis of AMI was also investigated. A total of 75 patients with AMI and 70 individuals without coronary heart disease were selected to participate in the present study. The demographic and clinical information of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
4
17
0
Order By: Relevance
“…The expression of ACSL1 is significantly related to the degree of atherosclerosis in the coronary artery (39). it has been observed that acSl1 is upregulated in peripheral blood leukocytes of patients with acute Mi (39). The present study further demonstrated the important roles of hsa-mir-142-3p and acSl1 in Mi.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The expression of ACSL1 is significantly related to the degree of atherosclerosis in the coronary artery (39). it has been observed that acSl1 is upregulated in peripheral blood leukocytes of patients with acute Mi (39). The present study further demonstrated the important roles of hsa-mir-142-3p and acSl1 in Mi.…”
Section: Discussionsupporting
confidence: 74%
“…overexpression of acSl1 can lead to severe cardiomyopathy (38). The expression of ACSL1 is significantly related to the degree of atherosclerosis in the coronary artery (39). it has been observed that acSl1 is upregulated in peripheral blood leukocytes of patients with acute Mi (39).…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of ACSL1 was an independent risk factor for AMI. The triglycerides content in peripheral white blood cells of patients with myocardial infarction was shown to increase [4]. Therefore, the high expression of ACSL1 gene increased the level of triglyceride, which has been hypothesized to be one of the pathogenesis of AMI promoted by ACSL1.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of total cholesterol, plasma triglyceride and plasma low-density lipoprotein (LDL) of AMI patients are significantly higher than those of healthy individuals. The results of our previous gene chip study suggested that the expression of ACSL1 in peripheral white blood cells (PBL) of AMI patients and healthy controls groups significantly increased (LogFC=2.590, P=0.04) [4]. The long-chain acyl-coenzyme A synthetases (ACSL) family played a key role in regulating fatty acids Ivyspring International Publisher which entered the synthetic or oxidative pathways [5].…”
Section: Introductionmentioning
confidence: 99%
“…The gene was associated with concentration of IDL particles in this study ( p = 1.82 × 10 −7 ), and its deficiency in the liver has been shown to reduce synthesis of triglycerides and beta oxidation, and alter the fatty acid composition of major phospholipids [37]. An intronic variant (rs60780116) in ACSL1 has been associated with T2D [38] and elevated expression of ACSL1 has been shown to be an independent risk factor for acute myocardial infarction [39].…”
Section: Discussionmentioning
confidence: 90%